Drying of oil palm lumber by combining air-force and modified super fast drying method - Mohd Nazip, Muhammad Nadzim (2019)
Having a unique wood structure and very high moisture content (MC), the drying has been one of big challenges in the utilization of oil-palm lumber (OPL). Drying of OPL took very long time and creates many defects. For any utilization, the wood needs to be dried. Since the drying of OPL took very long time and creates many defects, and also not all parts of OPL can be processed, the utilization of OPL becomes not economically attractive to the wood industry. An efficient method for drying of OPL needed to introduce. Basically, a new efficient drying method suitable for OPL has been introduced, i.e. “Super-Fast Frying” (SFD). The SFD was patented by Bakar et al. (2016) to solve the drying problems of OPL. This method is very efficient which can dry both outer and inner parts of OPL in not more than 3 hours. However, this SFD method involves the holing of the lumber before proceeding to the two-stage drying, the hot pressing and high temperature drying. These holes limit the application of super-fast dried OPL. On top of that, the method is quite complex since the processes is different for inner and outer OPL. Therefore, there is a need to improve the SFD method that capable to dry OPLs without involving the holing and the same processing procedure for inner and outer OPL. In our preliminary study it was found that the “Super-fast drying” can be made without holing when the MC of OPL is reduced. So in this study we are developing a “Modified Super-fast drying” method, (MSFD) in which the MC before the “Super-fast drying” is reduced to a certain intermediate MC. So, the “Modified Super-fast drying” method process consists of pre-drying (Air force drying) (AFD), hot-pressing and high-temperature drying. A series of intermediate MC of 100, 80 and 60% with AFD is tested and optimized based on drying performance (drying time, drying defects) and physical and mechanical properties of super-fast dried OPLs. The AFD was to determine the acceptable OPL thickness based on the drying performance in achieving the intermediate MCs. The MSFD was the comparison between “Super-fast drying” and “Modified super-fast drying” method in term of total drying time and super-fast dried OPL properties. The drying rates, physical and mechanical properties of dried OPLs were analyzed. The result showed that the AFD method dries OPLs at a faster rate than AD with very minor defect. The AD took very long time with a drying rate of (1.64-3.65 % per day) and create many defect (100 %) as compare to AFD (2.98-6.57% per day). This suggests that AFD can be used as pre-drying in the “Modified super-fast drying” method. The Modified super-fast drying can be made without holing by using intermediate MC between 100-60%. The process less complicated since the outer and inner OPLs can undergo the same procedure. All tested intermediate MCs treatment (100, 80, 60%) gave no significant effect on the physical and mechanical properties of super-fast-dried OPL, that suggest the 100% is the best intermediate MCs in term of total drying time. Comparing among the drying methods, MSFD, AFD and SFD, it can summarized that the “Modified super-fast drying” takes longer time (1 to 2 weeks, 3 hours) than the “Super-fast drying” (3 hours), but provide better TS, WA and SMOE than the “Super-fast drying”. These are much better than the “Air drying” as it reduce the drying time and drying defects, as well as improve the mechanical properties (SMOE and SMOR). It can be concluded that the MSFD as the best drying method since it does not require the holing process and has better properties.